Antarctic Extremophiles: Biotechnological Alternative to Crop Productivity in Saline Soils - Acuña-Rodríguez, Ian S.; Hansen, Hermann; Gallardo-Cerda, Jorge; Atala, Cristian; Molina-Montenegro, Marco A. (Frontiers in Bioengineering and Biotechnology, 2019)
High salinity results in osmotic stress and it can negatively impact plant grow and survival. Some plant species, however, can tolerate salinity by accumulating osmolytes like proline and maintaining low Na+ concentrations inside the cells. Another mechanism of saline stress tolerance is the association with symbiotic microorganism, an alternative that can be used as a biotechnological tool in susceptible crops. Those symbionts found in the Antarctica seems to be the ones with most potential since they (and their host) evolved in harsh and stressful conditions. We evaluated the effect of the inoculation with a symbiont consortium isolated from an Antarctic plant on saline stress tolerance in different crops. To test this we established 4 treatments: i) uninoculated plants with no saline stress, ii) uninoculated plants subjected to saline stress (200 mM NaCl), iii) plants inoculated with the microorganism consortium with no saline stress, and iv) inoculated plants subjected to saline stress. First, we assessed the effect of symbiont consortium on survival of four different crops in order to obtain a more generalized response of this biological interaction. Second, in order to deeply the mechanisms involved in salt tolerance, in lettuce plants we measured the ecophysiological performance (Fv / Fm) and lipid peroxidation to estimate the impact of saline stress on plants. We also measured proline accumulation and NHX1 antiporter gene expression to search for possible mechanism of stress tolerance. Additionally, root, shoot, and total biomass was also obtained as an indicator of productivity. Overall, plants inoculated with microorganisms from Antarctica increased the fitness related traits in several crops. On the other hand, saline stress negatively impacted all measured trait, but inoculated plants were significantly less affected. Under osmotic stress, Fv / Fm, proline accumulation and NHX1 expression was significantly higher and lipid peroxidation lower in inoculated plants compared to uninoculated individuals. Moreover, inoculated plants exposed to saline stress had a similar final biomass (whole plant) compared to individuals under no stress. We conclude that Antarctic extremophiles can effectively reduce the physiological impact of saline stress and highlight the Antarctica as a key source of microorganism with high biotechnological potential.